Die Zukunft der Dinge. Imaginationen von Unfall und Sicherheit - Eva Horn (Behemoth : a Journal on Civilisation, 2011)
This article examines cultural imaginings of the accident, understood as aesthetic forms of copingwith both the accident’s structural imperceptibility and the impossibility of its representation. Bydistinguishing between the normal and statistically expected accident on the one hand, and the absolutelyimprobable accident on the other, this paper discusses the way in which causal relationsand their latency can be observed and reconstructed through different narrative structures. Whilethe improbable accident seems to invoke animist notions of the ticklish object, the blurred relationsof causality extend to the future and enact new concepts of security such as the ‘precautionaryprinciple’.